Desalinisasi Tanah dalam Rehabilitasi Lahan yang Terkontaminasi Air dan Lumpur Laut Akibat Tsunami - Boiran Boiran; Muyassir Muyassir; Muktar Alba (Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Soil the Salinization with Some Use Ameliorance and Washing to Rehabilitating Land Affected by Water and Sediment Mud of Sea Effect of TsunamiABSTRACT. The aim of the research is to find ameliorant and the amount water use to leach the salt from the soil. The research was conducted with (1) to analyzed the soil sample, water that used for leach, and leached from leaching soil and (2) to set up and pot experiment by using maize as plant indicator. The plant is fertilized by adding urea, SP 36 and KCl with normal doses. This research set up by factorial Randomized Block Design with two factors, that is 3 types of ameliorant and 5 levels of leach soil. The result data was processed with analysis of variance and then to differentiate mean among each treatment and its interaction using Duncan Multiple Range Test at level 0,05. The result of this research showed that the effect of ameliorant for soil desalinization is significantly different to electroconductivity (ECe), the content of Na+, K+, Ca++, Mg++, SO4–, and Cl- ions of the leached, and to the maize height at 15, 30, 45 days after planting, dry cob weight, dry seed weight, and 100 dry maize seed weight. While treatment of leaching of soil significantly different to pH, and the others is the same with affected by ameliorant except for the data of the plant. While the effect of interaction treatment also significantly different to pH, electroconductivity (ECe) the content of Na+, K+, Ca++, Mg++, SO4–, and Cl- ions of the leached, and to the maize height at 15, 30, 45 days after planting, dry cob weight, dry seed weight, and 100 dry maize seed weight. Eventhough gypsum give a good result in this experiment but due to the difficulty to get this material it is recommended to use limestone+manure as ameliorant for desalinization of salted soil and to leach the soil can utilize P4 (4xLR) temporarily. Then in order to know the correct doses for desalinization of salted soil hence require to be done the further research use limestone+manure and combine by adding amount and frequency of irrigate leach.